Import Substitution with Labor Misallocation - Martins, Marco A.C. (World Bank, Washington, DC, 2018)
This paper argues that relying on major policy distortions to create a domestic automotive industry through import substitution generates significant costs for the economy, in terms of foregone output, lower consumption, and reduced overall welfare. To bring this issue into sharp relief, the paper focuses on the extreme case of an outright vehicle import ban (complemented by an export subsidy), which gives rise to a misallocation of resources that will ultimately reduce the overall productivity of labor. More specifically, a share of the labor force is diverted to the production of previously-imported vehicles, which would have not happened in the absence of import restrictions. In particular, the output of the final good goes down; consumption is lowered; and overall welfare is reduced. Importantly, the equilibrium stock of vehicles available in this economy is also reduced, defeating the purpose of the imposition of import substitution. Additionally, the creation of an automotive sector is not neutral with respect to factor prices: the resulting lower wages imply that revenues in the newly-created sector are generated at the expense of labor income. Technological change in the automotive industry might act as a countervailing force for labor misallocation, albeit only partially.